THE ISSUES OF PROGRAM CONTENT AND JOURNALISTIC SKILLS IN PRIVATE TV CHANNELS - Sabina Fayzullayeva (Bright Mind Publishing, 2025)
This article analyzes the program content and professional competence of journalists working in private television channels in Uzbekistan. With the expansion of the information space, increased competition among mass media, and changing audience demands, new requirements are being placed on program policy and journalist training. In particular, the relevance and quality of content, approaches to covering social issues, methods of engaging with the audience, and the competence of journalists in presenting information are considered as key aspects of analysis. The article examines the content strategies and journalistic approaches used by leading private TV channels in Uzbekistan, identifying existing problems and proposing solutions. The research aims to enhance the skills of students in pedagogical fields in working with mass media.
Keywords: Private TV channel, program content, journalistic skills, information quality, audience needs, mass media, media competition, professional training.